Paraguay, un camino hacia la democracia / Ramiro Barboza, Dionisio Borda, José Carlos Rodríguez - Borda, DionisioRodríguez, José Carlos; Barboza, Ramiro (Cuadernos laborales de América y España)
Bibliografía